2014
DOI: 10.1155/2014/580861
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Balance Training with Video Game-Based Therapy in Subacute Stroke Patients: A Randomized Controlled Trial

Abstract: The video game-based therapy emerged as a potential valid tool in improving balance in several neurological conditions with controversial results, whereas little information is available regarding the use of this therapy in subacute stroke patients. The aim of this study was to investigate the efficacy of balance training using video game-based intervention on functional balance and disability in individuals with hemiparesis due to stroke in subacute phase. Fifty adult stroke patients participated to the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
117
2
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 26 publications
1
117
2
14
Order By: Relevance
“…There is low and very low evidence that VR therapy improves walking ability [6,7,13,19]. According to our findings, training with Nintendo Wii™ on postural balance probably had positive effects on reducing the need for aids and/or supervision during walking for avoiding the risk of falling [19].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There is low and very low evidence that VR therapy improves walking ability [6,7,13,19]. According to our findings, training with Nintendo Wii™ on postural balance probably had positive effects on reducing the need for aids and/or supervision during walking for avoiding the risk of falling [19].…”
Section: Discussionmentioning
confidence: 56%
“…Compare to conventional balance therapy, Wii Fit gaming is effective on walking ability (FAC) and functional balance (FMBS) improvements in our study group. In an earlier study, partial benefits were observed in walking ability recovery on the follow-up [19]. There is low and very low evidence that VR therapy improves walking ability [6,7,13,19].…”
Section: Discussionmentioning
confidence: 94%
“…The results presented in the previous studies, 8,12 which applied only scales as tools for evaluating the balance, indicated the improvement of PC after the intervention with Wii Fit, however the studies which applied the posturography for evaluating the PC did not find significant statistical differences in the variables analyzed in the force platform, except for Barcala et al…”
Section: Discussionmentioning
confidence: 84%
“…7 The treatment methods for rehabilitating patients with stroke are based on the motor learning principles, in which the repetitive and intensive practice of a specific task induces cerebral plasticity modifications and influences the functional recovery of the deficits. 8,9 It is known, however, that the conventional therapies promote a limited amount of repetitions, 9 whereas therapies with virtual reality (VR) [10][11][12] have become promising, once they allow intensive and repetitive training of one single task. 8 VR is described as form of interface between the user and the computer that simulates a real environment and that allows the patients to interact with it.…”
Section: Intrductionmentioning
confidence: 99%
“…Because of the potential relevant characteristics of VR for motor learning and neuroplasticity [14], VR may be of even more added value during the earlier rehabilitation phase. Three studies [24][25][26] that investigated the effect of VR in this time period after stroke indicated a positive effect of commercially available VR systems (Nintendo Wii Fit or IREX) on balance and/or gait recovery. However, the results of these studies cannot be generalised to the whole population of patients with stroke because included participants had a relatively high functional level regarding balance and gait at the start of the VR intervention.…”
Section: Introductionmentioning
confidence: 99%